Antioxidant Activity of Microalgae Extract Cosmarium sp. Using 2.2-Azinobis-(3-Ethylbenzothiazoline)-6-Sulfonic Acid (ABTS) Radical Cation Assay (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
The demand for natural antioxidants has increased due to the harmful effects of synthetic antioxidants, such as toxicity and carcinogenic properties. Microalgae face this requirement as they can produce numerous substances that have the potential to be antioxidants. This study aimed to evaluate the antioxidant activity of Cosmarium extracts using ABTS radical cation assay and identify compounds probably responsible for it. Dried biomass was extracted using hexane, ethyl acetate, and ethanol solvents using the maceration method. Extracts were partially purified with TLC and column chromatography. Compound identification was conducted using GC-MS analysis. The result showed that ethanol extract has the best activity with the IC50 at 55.95 ppm, followed by hexane and ethyl acetate extracts with IC50 as much as 104.339 ppm and 180.07 ppm, respectively. Two active fractions were selected fraction after partial purification with chromatographic analysis. Fraction 1 gave IC50 at 99.6 ppm while fraction 2 gave better IC50 at 53.562 ppm, both categorized as strong antioxidants. Compounds identification by GC-MS revealed that both fractions contain fatty acids compounds with 9.12-octadecadienoic acid (linoleic acid) and hexadecanoic acid (palmitic acid) as the dominant compound in fractions 1 and 2, respectively. This study gave insight into the potential of ethanol fraction from Cosmarium sp. as a natural antioxidant.